1970
DOI: 10.1108/eb026486
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Half‐life’ of Periodical Literature: Apparent and Real Obsolescence

Abstract: The expression ‘half‐life’, borrowed from physics, has appeared quite frequently in the literature on documentation since 1960, when an article by Burton and Kebler on The ‘half‐life’ of some scientific and technical literatures was published, although it had certainly been used previously. Burton and Kebler point out that literature becomes obsolescent rather than disintegrating (as in its original meaning), so that ‘half‐life’ means ‘half the active life’, and this is commonly understood as meaning the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

1979
1979
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 0 publications
1
42
0
3
Order By: Relevance
“…NIELSEN [2007] points to this same fact in the growth of the Web, where the growth follow a power law increase in the initial years and them an exponential growth in the mature years of the Web. Exponential distributions are usual in scientometrics studies as scientific literature obsolescence [LINE, 1970;1993] and e-journal usage along the time [NICHOLAS & AL., 2005]. Although some papers have shown similar singularities in the fit of these distributions [EGGHE & RAVICHANDRA, 1992;BURRELL, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…NIELSEN [2007] points to this same fact in the growth of the Web, where the growth follow a power law increase in the initial years and them an exponential growth in the mature years of the Web. Exponential distributions are usual in scientometrics studies as scientific literature obsolescence [LINE, 1970;1993] and e-journal usage along the time [NICHOLAS & AL., 2005]. Although some papers have shown similar singularities in the fit of these distributions [EGGHE & RAVICHANDRA, 1992;BURRELL, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Many years ago, it was suggested that given the accelerated pace of scientific development, scientific literature becomes more rapidly obsolete (Line 1970(Line , 1993Price, 1963Price, , 1965. Along those lines, the widespread use in some fields of open-access and e-print servers such as arXiv provides scientists with more rapid access to new research.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, applied sciences create patents which contain detailed description of inventions, while the humanities need books which permit the expression of textual criticism and speculative and discursive reasoning. Disciplines with a rapid obsolescence tend to use fast communication media such as the proceeding papers (Line, 1970). This involves assessing the scientific research according to multiple output indicators which express the different activities of each research discipline (Martin, 1996).…”
Section: Introductionmentioning
confidence: 99%